Crab barrel syndrome: Looking through the lens of type A and type B personality theory and social comparison process - Uzum, Burcu; Ozdemir, Yasemin; Kose, Semra; Ozkan, Osman Seray; Seneldir, Okan (Frontiers in Psychology, 2022)
The main purpose of this study is to identify the precursors of crab barrel syndrome. In line with this main purpose, the study also aims to reveal the relationship between crab barrel syndrome behaviours and type A versus type B personalities, along with the effect of social comparison behaviours. It is designed quantitatively, employing scales to quantify type A and type B personalities, social comparison, and crab barrel syndrome. Hypotheses are tested using structural equation modeling. It is found that there is a positive relation between the type A personality and the crab barrel syndrome, and a negative one between the syndrome and self-esteem. Type A personality represents the personalities of individuals who are stressed, ambitious, competitive, and quickly take action for their aims. Type B, on the other hand, presents the personality types of individuals who are calm, away from competition, and perform their actions slowly. The findings show that social comparison and type A personality are the precursors of crab barrel syndrome. The limitations of the research are discussed and suggestions are made for future research.